SGK1 Mediates Hypoxic Pulmonary Hypertension through Promoting Macrophage Infiltration and Activation - Xin Xi; Jing Zhang; Jian Wang; Yuqin Chen; Wenmei Zhang; Xiaoping Zhang; Jie Du; Guangfa Zhu (Analytical Cellular Pathology)
Inflammation plays a pivotal role in the development of pulmonary arterial hypertension (PAH). Meanwhile, serum glucocorticoid-regulated kinase-1 (SGK1) has been considered to be an important factor in the regulation of inflammation in some vascular disease. However, the role of SGK1 in hypoxia-induced inflammation and PAH is still unknown. WT and SGK1-/- mice were exposed to chronic hypoxia to induce PAH. The quantitative PCR and immunohistochemistry were used to determine the expression of SGK1. The right ventricular hypertrophy index (RVHI), RV/BW ratio, right ventricle systolic pressure (RVSP), and percentage of muscularised vessels and medical wall thickness were measured to evaluate PAH development. The infiltration of macrophages and localization of SGK1 on cells were examined by histological analysis. The effects of SGK1 on macrophage function and cytokine expression were assessed by comparing WT and SGK1-/- macrophages in vitro. SGK1 has high expression in hypoxia-induced PAH. Deficiency of SGK1 prevented the development of hypoxia-induced PAH and inhibited macrophage infiltration in the lung. In addition, SGK1 knockout inhibited the expression of proinflammatory cytokines in macrophages. SGK1-induced macrophage activation and proinflammatory response contributes to the development of PAH in hypoxia-treated mice. Thus, SGK1 might be considered a promising target for PAH treatment.